The politics of irony in American modernism - Stratton, Matthew; ebrary, Inc. (New York : Fordham University Press, 2014)
"This book shows how American literary culture in the first half of the twentieth century saw "irony'" emerge as a term to describe intersections between aesthetic and political practices. Against conventional associations of irony with political withdrawal, Stratton shows how the term circulated widely in literary and popular culture to describe politically engaged forms of writing. It is a critical commonplace to acknowledge the difficulty of defining irony before stipulating a particular definition as a stable point of departure for literary, cultural, and political analysis. This book, by contrast, is the first to derive definitions of "irony" inductively, showing how writers employed it as a keyword both before and in opposition to the institutionalization of New Criticism. It focuses on writers who not only composed ironic texts but talked about irony and satire to situate their work politically: Randolph Bourne, Benjamin De Casseres, Ellen Glasgow, John Dos Passos, Ralph Ellison, and many others"--
Machine generated contents note: -- Introduction: Irony and How It Got That Way -- Chapter 1: The Eye in Irony: New York, Nietzsche, and the 1910s -- Chapter 2: Gendering Irony and Its History: Ellen Glasgow and the Lost 1920s -- Chapter 3: The Focus of Satire: Irony and Public Opinions of Propaganda in the U.S.A. of John Dos Passos Page -- Chapter 4: Visible Decisions : Irony, Law, and the Political Constitution of Ralph Ellison -- Beyond Hope and Memory: A Conclusion -- Bibliography.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: American literature -- 20th century -- History and criticism; Irony in literature; Satire -- History and criticism; Politics in literature; Politics and literature -- United States -- History -- 20th century; Politics and culture -- United States -- History -- 20th century; Literature and society -- United States -- History -- 20th century; Modernism (Literature) -- United States; Electronic books